User Experience Analysis on the Karanganyar People's Market (Semarak) Online System Website at the Karanganyar Regency Communication and Information Service Using the User Experience Questionnaire (Ueq) Approach - Bachtiar, Hafid Fikri; Efrilianda, Devi Ajeng (Journal of Advances in Information Systems and Technology, 2023)
Technological developments have made government agencies at various levels start using e-Government services. The purpose of this study is to determine the application of e-government on websites. The method used in this study is a quantitative method using the User Experience Questionnaire (UEQ) with a data processing tool, namely the UEQ Data Analysis Tool software. available in the form of an Excel application. The results of the descriptive statistical analysis on each UEQ variable can be seen that the Karanganyar Online People's Market System (Semarak) website gets a positive rating value on the variables interestingness (mean 1.41), perspicuity (mean 1.41), efficiency (mean 1.69 ). , dependence with (average 1.31), stimulation (average 1.08). While the novelty variable gets a neutral evaluation (mean 0.69).